Produksi Metabolit Sekunder Torbangun (Coleus amboinicus Lour.) Pada Berbagai Umur Panen - Moh. Ega Elman Miska; Silvina Malasari (Jurnal Agroekoteknologi, 2026)
Torbangun is a functional plant derived from vegetable plants that can increase breast milk production and reduce cholesterol so that it has the potential as a source of lactogagum and antihyperlipidemia. Bioactive compounds in torbangun leaves that act as a source of lactogagum and antihyperlipidemia are flavonoids and saponins. The torbangun plant that is consumed is the leaf part. The development of torbangun in the manufacture of medical simplicia standards is constrained by the best harvest time. The purpose of the study was to determine the best torbangun harvest time to achieve optimal metabolic production. The method used was a Randomized Block Design with a single factor, namely harvest time. Harvest time consists of 8, 12, 16, 20 and 24 WAP (Weeks After Planting). Each treatment was repeated 4 times, so there were 20 experimental units. The results showed that the torbangun harvest time of 8 WAP produced a total flavonoid concentration of 10.00 mg QE g-1 DB, the harvest time of 24 WAP produced 12.30 mg of saponin g-1 DB total saponin concentration and the harvest time of 20 WAP produced a quercetin concentration of 3.46 mg g-1 DB.